Hubungan Antara Kualitas Perawatan Kateter Dengan Kejadian Infeksi Nosokomial Saluran Kemih - Kasmad, Kasmad; Sujianto, Untung; Hidayati, Wahyu (Department of Nursing, Faculty of Medicine, Diponegoro University, 2007)
Nosocomial infection refer to occurrence the often happen in hospital and can causes import to patient, family and hospital of self. Once of infection that often happened is infection of urinary tract at the patient with dower chateter. Factors that caused nosocomial infection of urinary tractare hospes, agent, installation procedure, old of installed chateter and quality of chateter treatment. This research ago to know the quality chateter treatment with the occurrence of nosocomial infection urinary tract. The research method is observation and the instrument used observation sheet. Independent variable in this research is the quality of chateter treatment and for the dependent variable is occurrence as nosocomial infection of urinay tract. The research subject is cause who had Diploma degree and Graduate of nursing, male patient that treated in Roemani’s Hospital, wear installed dower chateter, age of respondent between 18 – 55 years old, medic diagnose was not tractus urinarius infection, not consume antibiotic and agree to be respondent. Amount of sample are 30 respondents. Result of this research showed that the must quality of treatment chateter is enough (50%), good (30%) and less (20%). Number of occurrence of nosocomial infection of urinary tract that got chateter treatment with good quality was 22.22%, enough 26.67% and less 83.33%. To decrease the occurrence of nosocomial infection of urinary tract that cause by installing of chateter was need the increasing the quality of chateter treatment that appropriate to the nursing procedure standart and the pressed of infection prevention. Statistic test used Chi Square test to examine the relation between the quality of chateter treatment with the occurrence of nosocomial infection of urinary tract. Chi Square analisis result t count (7.081) > t table (5.99) and p value (0.029) < 0.05. Which means that there is relation between quality of chateter treatment with the occurrence nosocomial infection of urinary tract.